Disciplinary directors: Evidence from the appointments of outside directors who have fired CEOs - Cai, Jay; Nguyen, Tu (Journal of Banking & Finance, 2018)
By examining board appointments of outside directors who have previously fired a CEO, we study how directors’ willingness to take disciplinary actions is related to a firm's performance and risk-taking. Such directors (‘disciplinary directors’) appear to benefit firms with weak monitoring, but hurt firms in innovative industries. Firms appointing a disciplinary director subsequently exhibit lower idiosyncratic risk, leverage, and R&D expense, make fewer acquisitions, and are more likely to replace poorly performing CEOs. Overall, disciplinary directors appear to influence managerial behavior and shareholder wealth.